Association of screen time to the dietary intake, BMI, and sex of College of Home Economics students at the University of the Philippines Diliman - Almazan, Karyssa Marielle R.; Callejo, Kenneth R.; Tugas, Emmalyn T. (College of Home Economics, University of the Philippines Diliman, 2023)
Screen time significantly increased during and post-COVID-19 pandemic as it served as the main mode of communication, especially for the purpose of social connection and the provision of education through remote learning. However, excessive screen time has already become a public health concern as recent research shows its negative impact on health, some of which being related to unhealthy dietary intake and higher Body Mass Index (BMI), with varying data on sex. Even so, most studies lack focus on college students, as existing studies are centered primarily on children. This study determined the association of screen time to the dietary intake, BMI, and sex of the students of College of Home Economics (CHE) at the University of the Philippines Diliman. The study was completed following a descriptive correlational design. The participants consisted of 27 enrolled undergraduate students from the CHE at the University of the Philippines Diliman. Three (3) food records were accomplished on two non-consecutive weekdays and one weekend to measure dietary intake, along with three (3) screen time records on the same day the records were completed. Screen time was assessed through self-measurement and the use of Stayfree, an automatic time log application and browser extension. BMI was computed and interpreted based on weight and height assessments. The collected data were processed and analyzed using weighted mean, frequency and percentages, Spearman's Rho Correlation, and the Chi-Square Test of Independence to examine the relationships among the variables of interest. Among all nutrients, only potassium showed a weak positive correlation with educational screen time. No correlation was found between recreational screen time and dietary intake. There was also no significant correlation between screen time (both educational and recreational) and BMI and sex. The results suggest that there is a weak tendency for CHE students who spend more time on screens to consume higher levels of potassium in their diet. More research involving a higher number of participants is needed to substantiate this association.